Athletes as role models during the COVID-19 pandemic. Issue 1 (4th March 2022) - Leng, Ho Keat; Phua, Yi Xian Philip
ABSTRACT: Athletes are considered potential role models for young adults even though some of them exhibit inappropriate behaviours. In this commentary, the paper begins with a description of inappropriate behaviours of some athletes during the current COVID-19 pandemic. In this age of social media, news of such inappropriate behaviour can spread very quickly, particularly when the behaviour evokes an emotive response. However, social media can also be leveraged to spread positive messages. During this pandemic, athletes like other celebrities can be role models. They can encourage appropriate behaviours including social distancing to stem the spread of the virus through social media. The paper ends with a short discussion on the future of athletes as role models during a pandemic.